From pea soup to water factories: wastewater paradigms in India and the Netherlands. Issue 115 (January 2021) - Vij, Sumit; Moors, Eddy; Kujawa-Roeleveld, Katarzyna; Lindeboom, Ralph E.F.; Singh, Tanya; de Kreuk, Merle K.
Highlights: There is limited scholarship on wastewater paradigms. India's wastewater paradigms have changed from 'water resource to meet basic human needs' to 'water scarcity and beautification of cities'. In the Netherlands, the wastewater paradigms have shifted from 'public health and environmental concerns' to the 'circular economy of wastewater'. Indian wastewater policy domain are yet to design appropriate financial and technical instruments to improve urban wastewater treatment capacity and reuse. Abstract: Freshwater scarcity has increased in the cities of the global South due to rapid urban agglomeration and changing climate. Alternative water resources such as treated wastewater can play a significant role to reduce the water supply-demand gap. In the recent past, wastewater has been used solely for irrigation and other allied agriculture purposes, with limited focus on reuse for other purposes within the cities. Despite the progress in wastewater treatment technology and various policy frameworks, in low income and lower-middle-income countries, limited progress has been made. Through this article, we compare three aspects, representing the wastewater paradigms in India and the Netherlands. The three elements are 1) framing, 2) policy goals, and 3) technical and financial instruments. Using policy document analysis and interviews, we compare water and related policies prepared in India and the Netherlands. We found that the wastewater paradigms have evolved in the two countries. In India, the wastewater paradigms have realized paradigm changes from 'water resource to meet a basic human need' to 'water as an engine of economic growth' and then to 'water scarcity and beautification of cities'. In the case of the Netherlands, the wastewater paradigms have changed from an emphasis on 'public health and environmental concerns' to the 'circular economy of wastewater'. Although the Netherlands has to still meet the water quality targets of the European Water Directive Framework with regards to micropollutants, the country has made significant progress towards wastewater treatment and reuse in the last four decades. On the contrary, the Indian wastewater policy domain has room for improvement in terms of designing appropriate financial instruments and governance strategies to increase the urban wastewater treatment capacity and reuse. This article concludes that the use of the concept of wastewater paradigm is useful to show the progress and challenges in the two countries.